#TITLE_ALTERNATIVE# - PRIMA H (NIM 10107084); Pembimbing : Sumanto W.H, M.Comp., ARIZA
Variations in manufacturing processes are expected to fluctuate around a constant level called the process mean. This article is concerned with the development of a control chart that detects cycles in the process mean. The new control chart, the spectral control chart, is based on the periodogram. The value plotted at each point in time is the ratio of the largest periodogram ordinate to the average of all ordinates. When an observation falls above the prescribed control limit, an out-of-control signal is given. The spectral control chart is compared with X control chart, R control chart, and Cusum control chart to detect variations. Spectral control chart is useful for detecting cyclic variatons rather than detecting shift in the process mean. The spectral control chart should be used along with existing control charts so that both shifts and cycles in the process mean can be detected.